Experimental Disease-Modifying Agents for Frontotemporal Lobar Degeneration - Giunta M; Solje E; Gardoni F; Borroni B; Benussi A (Dove Medical Press, 2021)
Marcello Giunta,1 Eino Solje,2 Fabrizio Gardoni,3 Barbara Borroni,1 Alberto Benussi1 1Neurology Unit, Department of Clinical and Experimental Sciences, University of Brescia, Brescia, Italy; 2Institute of Clinical Medicine - Neurology, University of Eastern Finland, Kuopio, Finland; 3Department of Pharmacological and Biomolecular Sciences, University of Milan, Milan, ItalyCorrespondence: Alberto BenussiClinica Neurologica, Università degli Studi di Brescia, P.le Spedali Civili, 1, Brescia 25100, ItalyTel +39 0303995632Email benussialberto@gmail.comAbstract: Frontotemporal dementia is a clinically, genetically and pathologically heterogeneous neurodegenerative disorder, enclosing a wide range of different pathological entities, associated with the accumulation of proteins such as tau and TPD-43. Characterized by a high hereditability, mutations in three main genes, MAPT, GRN and C9orf72, can drive the neurodegenerative process. The connection between different genes and proteinopathies through specific mechanisms has shed light on the pathophysiology of the disease, leading to the identification of potential pharmacological targets. New experimental strategies are emerging, in both preclinical and clinical settings, which focus on small molecules rather than gene therapy. In this review, we provide an insight into the aberrant mechanisms leading to FTLD-related proteinopathies and discuss recent therapies with the potential to ameliorate neurodegeneration and disease progression.Keywords: frontotemporal dementia, frontotemporal lobar degeneration, therapy, TDP-43, tau, C9orf72, GRN, MAPT